Perbandingan Plat Hollow Core Slab (HCS) Dan Cast In-Situ : Biaya, Dan Waktu (Studi Kasus : Project Museum Al-Kitab GBI Summarecon Bandung) - Ma'sum Alanur Ridwan; Siti Nurasiyah; Istiqomah - (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
A In the construction industry, there are two primary methods for concrete work: the conventional method (cast in situ) and the precast method. This study compares existing conventional floor slabs in the Al-Kitab GBI Summarecon Bandung Museum project with the precast Hollow Core Slab (HCS) system as an alternative modification. The conventional method is carried out directly on-site, requiring extensive formwork, labor, and strict supervision, resulting in a longer construction timeline. The precast HCS method does not require formwork, offers better quality control as it is manufactured in a factory, and requires less labor, although it necessitates heavy machinery for the installation of structural elements. The differences in characteristics between these two methods impact construction costs and the duration of the work. This study employs a quantitative descriptive approach tailored to the research variables, focusing on current issues and construction phenomena. The analysis compares the two construction methods based on two main aspects: cost and construction time, focusing on floor slab structures. Based on the analysis of the two floor slab methods—cast-in-place and precast hollow core slab (HCS)—it was found that the precast HCS slab system has an advantage in terms of construction time, being 46 days or 29.3% faster than the cast-in-place method. However, in terms of cost, the precast HCS method is more expensive by Rp264,422,444.67 or 4.11% compared to the cast-in-place method.